Implementasi Algoritme Support Vector Machines untuk Klasifikasi Area Terbakar di Lahan Gambut - Edi Saputra; Ulfa Khaira; Zainil Abidin (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
Forest fires have become annual disasters in Indonesia and have an impact on peatland degradation. Many forest fires occur on peatlands. In August 2019, 810 hotspots were detected in Jambi Province. Burned area of peatland information is needed so that the goverment can determine policy on the effectiveness and efficiency of forest management. Information about burned area of peatland is difficult to obtain from field measurements because the area is large and not easily accessible. Landsat data is a type of image from remote sensing technology that can be used to map this area. One method that is often used to estimate the burned area is visual on-screen interpretation. However, this technique requires experienced interpreters. For this reason, this study used digital interpretation techniques using the Support Vector Machine (SVM) algorithm to classify burned area, vegetation, and bare soil from remote sensed data of protected area of peat in Muaro Jambi District, Jambi Province. This study obtained a classifier with the accuracy of 99.8%. The estimated area of peat based on the SVM classifier on August 15th 2019 are 1,396.89 hectares at the burned area class, 7,069.5 hectares at the vegetation class, and 1,089.54 hectares at the bare soil class.